Transparent antibacterial polycarbonate resin composition and molded article thereof
By adding silver-based glass antibacterial agent to the polyamide-polysiloxane copolymer resin, the problem that polyamide resin in the prior art is difficult to add antibacterial properties on the basis of maintaining transparency and impact resistance, achieving efficient antibacterial effects and preservation of original properties.
Patent Information
- Application Number
- JP2021018862
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-09
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2041-02-09
AI Technical Summary
The prior art is difficult to add effective antibacterial properties to polyamide resins on the basis of maintaining transparency and impact resistance.
Add silver-based glass antibacterial agent to the polyamide-polysiloxane copolymer resin to enable it to release silver ions, thereby achieving antibacterial effect. At the same time, the transparency and impact resistance of the polyamide resin are maintained through reasonable formulation and processing technology.
It realizes the antibacterial properties of polyamide resin, while maintaining its original transparency and high impact resistance, and is suitable for a variety of application scenarios.
Smart Images

Figure 0007656436000001 
Figure 0007656436000002 
Figure 0007656436000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a transparent antibacterial polycarbonate resin composition and a molded article thereof. More specifically, the present invention relates to a transparent antibacterial polycarbonate resin composition and a molded article thereof, the transparency and impact resistance of which are improved by adding a silver-based glass antibacterial agent to a polycarbonate-polydiorganosiloxane copolymer resin. [Background technology]
[0002] Polycarbonate resins are generally used in many applications, such as machine parts, automobile parts, electric and electronic parts, and office equipment parts, due to their excellent properties, such as excellent transparency, impact resistance, heat resistance, dimensional stability, and flame retardancy. In recent years, in order to prevent the spread of known and unknown pathogens, as well as in consideration of hygiene and cleanliness, there is a demand for materials with antibacterial properties for the exterior and various parts of products that can be used by an unspecified number of people, such as home appliances such as toilets, home appliances such as refrigerators and air conditioners, medical equipment, ATMs (automated teller machines) installed in convenience stores, POS terminals, mobile phones, and smartphones.
[0003] As a method for imparting antibacterial properties to polycarbonate resin, a method of adding various phosphorus-based or phenol-based antioxidants, heat stabilizers, and acid-modified olefin waxes to inorganic antibacterial agents (for example, calcium phosphate, zeolite, zirconium phosphate, etc. carrying antibacterial metal ions such as silver, copper, and zinc) has been proposed (Patent Documents 1 to 3), but the antibacterial properties were not sufficient. As a method for improving antibacterial properties, a method of using silver-based and zinc-based antibacterial agents in combination (Patent Document 4) has been proposed, but various properties when added to a polycarbonate resin composition were not sufficient. As a method for imparting antibacterial properties without impairing the characteristics of polycarbonate resin, a method of adding an antibacterial agent containing glass that elutes silver ions (Patent Document 5) and a method of blending a zinc-based glass antibacterial agent and a silver-based zirconium phosphate antibacterial agent in a specific ratio (Patent Document 6) have been proposed, but the former does not sufficiently suppress the decrease in impact resistance and heat resistance, which are generally sacrificed by adding a glass component, and the latter is recognized as maintaining impact resistance, but transparency and heat resistance are sacrificed, and have not been considered. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 6-240125 [Patent Document 2] Japanese Patent Application Publication No. 10-168294 [Patent Document 3] Japanese Patent Application Publication No. 11-323117 [Patent Document 4] JP 2007-217300 A [Patent Document 5] JP 2011-137068 A [Patent Document 6] JP 2017-132913 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a transparent antibacterial polycarbonate resin composition which exhibits antibacterial properties without impairing the transparency and impact resistance which are inherent characteristics of polycarbonate resins. [Means for solving the problem]
[0006] As a result of intensive research aimed at solving the above problems, the present inventors have discovered that a resin composition in which a silver-based glass antibacterial agent is added to a polycarbonate-polydiorganosiloxane copolymer resin exhibits antibacterial properties while simultaneously achieving both transparency and good impact resistance, and have thus completed the present invention. According to the present invention, the above problems are solved by the following configuration.
[0007] (Configuration 1) A transparent antibacterial polycarbonate resin composition comprising 100 parts by weight of (A) a polycarbonate-polydiorganosiloxane copolymer resin (component A-1) or a mixture (component A-1) of component A-1 and a polycarbonate resin other than component A-1 (component A-2) which comprises a repeating unit represented by the following general formula [1], and (B) 0.3 to 5 parts by weight of a silver-based glass antibacterial agent (component B) supported on glass so that silver ions are eluted, wherein the haze of a molded article having a thickness of 2 mm and made of the resin composition is less than 50%.
[0008] [ka]
[0009] [In formula [1], R 1 and R 2each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each, they may be the same or different, e and f each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following formula [2].
[0010] [ka]
[0011] [In formula [2], R 11 ,R 12 ,R 13 ,R 14 ,R 15 ,R 16 ,R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of groups, they may be the same or different, g is an integer from 1 to 10, and h is an integer from 4 to 7.
[0012] (Configuration 2) The transparent antibacterial polycarbonate resin composition according to the above-mentioned configuration 1, characterized in that the component A-1 is a polycarbonate-polydiorganosiloxane copolymer resin containing a repeating unit represented by the following general formula [3]:
[0013] [ka]
[0014] [In formula [3], R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number of 30 to 50. X is a divalent aliphatic group having 2 to 8 carbon atoms.]
[0015] (Configuration 3) In the above general formula [3], R 3 , R 4 , R 5 , R 6 , R 7 and R 8 3. The transparent antibacterial polycarbonate resin composition according to the above item 2, wherein is a methyl group.
[0016] (Configuration 4) The transparent antibacterial polycarbonate resin composition according to the above-mentioned configuration 2 or 3, characterized in that the repeating unit represented by the above-mentioned general formula [3] is a repeating unit derived from a (2-allylphenol)-terminated polydiorganosiloxane or a (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane.
[0017] (Configuration 5) 5. The transparent antibacterial polycarbonate resin composition according to any one of the above configurations 1 to 4, characterized in that the content of the A-1 component is 5 to 100 parts by weight per 100 parts by weight of the total of the A-1 component and the A-2 component.
[0018] (Configuration 6) 6. The transparent antibacterial polycarbonate resin composition according to any one of the above configurations 2 to 5, characterized in that the content of the polydiorganosiloxane block represented by the above general formula [3] is 0.5 to 20% by weight based on the total weight of component A.
[0019] (Configuration 7) 7. The transparent antibacterial polycarbonate resin composition according to any one of the above configurations 2 to 6, wherein component A-1 has an aggregate structure in which polydiorganosiloxane domains are dispersed in a polycarbonate resin matrix, and the polydiorganosiloxane domains have an average size of 5 to 15 nm and a normalized dispersion of 25% or less.
[0020] (Configuration 8) 8. The transparent antibacterial polycarbonate resin composition according to any one of the above configurations 1 to 7, wherein the average particle size (D50) of component B measured by a laser diffraction / scattering method is 7 to 15 μm.
[0021] (Configuration 9) 9. The transparent antibacterial polycarbonate resin composition according to any one of the above configurations 1 to 8, characterized in that it contains, relative to 100 parts by weight of component A, 0.01 to 0.1 parts by weight of (C) a phosphorus-based stabilizer (component C), 0.1 to 1 parts by weight of (D) a release agent (component D), and 0 to 1 parts by weight of (E) an ultraviolet absorbing agent (component E).
[0022] (Configuration 10) 10. A molded article obtained by molding the transparent antibacterial polycarbonate resin composition according to any one of the above items 1 to 9. Effect of the Invention
[0023] INDUSTRIAL APPLICABILITY The transparent antibacterial polycarbonate resin composition of the present invention is capable of providing molded articles that exhibit antibacterial properties without impairing the inherent characteristics of polycarbonate resin, such as transparency and impact resistance, and is useful for plastic parts related to toilets and washstands that can be used by an unspecified number of people, the exteriors of tablets, notebook computers, smartphones, digital cameras, medical monitors, POS, office machines, printers, televisions, etc., irons, hair dryers, rice cookers, microwave ovens, air conditioners, air purifiers, negative ion generators, various buttons and switches, doorknobs, amusement-related plastic parts, various vehicle-related plastic parts, etc., and the industrial effects achieved by the composition are exceptional. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] (Component A) Component A is a polycarbonate-polydiorganosiloxane copolymer resin (component A-1) or a mixture of component A-1 and a polycarbonate resin (component A-2) other than component A-1 that comprises a repeating unit represented by the following general formula [1]:
[0025] (A-1 component: polycarbonate-polydiorganosiloxane copolymer resin) In the present invention, the polycarbonate-polydiorganosiloxane copolymer resin (hereinafter sometimes abbreviated as PC-POS copolymer) is preferably a polycarbonate-polydiorganosiloxane copolymer resin containing a repeating unit represented by formula [3], and more preferably a polycarbonate-polydiorganosiloxane copolymer resin consisting of a polycarbonate block represented by formula [1] and a polydiorganosiloxane block represented by formula [3].
[0026] <Polycarbonate block represented by formula [1]> In the present invention, the polycarbonate block is represented by the following formula [1].
[0027] [ka]
[0028] [In formula [1], R 1 and R 2 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each of these groups, they may be the same or different, and e and f each represent an integer of 1 to 4. and W is a single bond or at least one group selected from the group consisting of groups represented by the following formula [2].
[0029] [ka]
[0030] [In formula [2], R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of groups, they may be the same or different, g is an integer from 1 to 10, and h is an integer from 4 to 7.
[0031] Examples of halogen atoms include fluorine, chlorine, and bromine atoms. Examples of alkyl groups having 1 to 18 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, and tetradecyl groups. Preferred are alkyl groups having 1 to 6 carbon atoms. Examples of alkoxy groups having 1 to 18 carbon atoms include methoxy, ethoxy, propoxy, butoxy, pentoxy, hexoxy, and octoxy groups. Preferred are alkoxy groups having 1 to 6 carbon atoms. Examples of cycloalkyl groups having 6 to 20 carbon atoms include cyclohexyl and cyclooctyl groups. Preferred are cycloalkyl groups having 6 to 12 carbon atoms. Examples of cycloalkoxy groups having 6 to 20 carbon atoms include cyclohexyloxy and cyclooctyloxy groups. Preferred are cycloalkyl groups having 6 to 12 carbon atoms. Examples of the alkenyl group having 2 to 10 carbon atoms include a methenyl group, an ethenyl group, a propenyl group, a butenyl group, and a pentenyl group. An alkenyl group having 2 to 6 carbon atoms is preferable. Examples of the aryl group having 6 to 14 carbon atoms include a phenyl group and a naphthyl group. Examples of the aryloxy group having 6 to 14 carbon atoms include a phenyloxy group and a naphthyloxy group. Examples of the aralkyl group having 7 to 20 carbon atoms include a benzyl group and a phenylethyl group. Examples of the aralkyloxy group having 7 to 20 carbon atoms include a benzyloxy group and a phenylethyloxy group.
[0032] Examples of the alkyl group having 1 to 18 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, and a dodecyl group. An alkyl group having 1 to 6 carbon atoms is preferable. Examples of the aryl group having 6 to 14 carbon atoms include a phenyl group, a naphthyl group, and the like. These may be substituted. Examples of the substituent include an alkyl group having 1 to 6 carbon atoms, such as a methyl group, an ethyl group, a propyl group, and a butyl group. Examples of the aralkyl group having 7 to 20 carbon atoms include a benzyl group, a phenylethyl group, and the like.
[0033] g is preferably an integer of 1 to 6. h is preferably an integer of 4 to 5.
[0034] The polycarbonate block represented by the formula [1] is preferably one derived from 2,2-bis(4-hydroxyphenyl)propane.
[0035] The length of the polycarbonate block is the average number of repeating units of the formula [1], and is preferably 10-100, more preferably 30-100, and even more preferably 50-70.
[0036] The content of the polycarbonate block represented by the formula [1] is preferably 50 to 99.9% by weight, more preferably 80 to 99.5% by weight, and even more preferably 90 to 99.0% by weight, based on the total weight of the PC-POS copolymer.
[0037] <Polydiorganosiloxane block represented by formula [3]> In the present invention, the polydiorganosiloxane block is represented by the following formula [3].
[0038] [ka]
[0039] [In formula [3], R 3 , R 4 , R 5, R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number of 30 to 50. X is a divalent aliphatic group having 2 to 8 carbon atoms.]
[0040] Examples of the alkyl group having 1 to 12 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, and a dodecyl group. An alkyl group having 1 to 6 carbon atoms is preferable. Examples of the substituted or unsubstituted aryl group having 6 to 12 carbon atoms include a phenyl group and a naphthyl group. Examples of the substituent include an alkyl group having 1 to 12 carbon atoms such as a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, and a hexyl group. R 3 , R 4 , R 5 , R 6 , R 7 and R 8 is preferably a methyl group.
[0041] Examples of halogen atoms include fluorine, chlorine, and bromine atoms. Examples of alkyl groups having 1 to 10 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, and dodecyl groups. Preferred are alkyl groups having 1 to 6 carbon atoms. Examples of alkoxy groups having 1 to 10 carbon atoms include methoxy, ethoxy, propoxy, butoxy, pentoxy, hexoxy, heptoxy, and octoxy groups. Preferred are alkoxy groups having 1 to 6 carbon atoms.
[0042] The divalent aliphatic group may be an alkylene group having a carbon number of 2 to 8. Examples of the alkylene group include an ethylene group, a trimethylene group, and a tetramethylene group.
[0043] The polydiorganosiloxane block represented by the above formula [3] is preferably a polydiorganosiloxane block derived from a (2-allylphenol)-terminated polydiorganosiloxane or a (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane. 9 and R 10 is a hydrogen atom, or X is a trimethylene group and R 9 and R 10 is preferably a methoxy group.
[0044] The content of the polydiorganosiloxane block represented by the above formula [3] is preferably 0.5 to 20.0% by weight, more preferably 1.0 to 18.0% by weight, even more preferably 2.0 to 15.0% by weight, and particularly preferably 3.0 to 10.0% by weight, based on the total weight of the PC-POS copolymer. If it is below the lower limit of the preferred range, not only will the desired refractive index of the PC-POS copolymer, which is important for expressing the transparency of the resin composition in the present invention, not be obtained, but the domain formation described below will be insufficient, and the improvement effect of impact resistance (particularly in a low-temperature environment such as -30°C) may not be fully expressed. On the other hand, if it exceeds the upper limit of the preferred range, major problems in terms of production such as polymerization reaction failure due to deterioration of the emulsion state or difficulty in granulation due to a too low glass transition temperature may occur, or the transparency and heat resistance of the PC-POS copolymer may decrease.
[0045] The viscosity average molecular weight of the A-1 component is preferably 11,000 to 30,000, more preferably 15,000 to 27,000, and even more preferably 18,000 to 25,000.Below the lower limit of this preferred range, it may be difficult to obtain practical mechanical strength in many fields, and the difference in melt viscosity with the polycarbonate resin (A-2 component) other than the A-1 component to be mixed may become large, resulting in poor melt-kneadability, while exceeding the upper limit of this preferred range may result in problems such as thermal deterioration of the resin and poor separation in the water washing step during production, leading to reduced productivity.
[0046] p+q is 30 to 50, and more preferably 30 to 45. If it is below the lower limit of this preferred range, a sufficient effect of improving impact resistance cannot be obtained, whereas if it exceeds the upper limit of this preferred range, excellent transparency cannot be achieved.
[0047] (A-2 component: polycarbonate resin other than A-1 component) The polycarbonate resin (A-2 component) other than the A-1 component in the present invention is derived from a dihydric phenol represented by the following general formula [4].
[0048] [ka]
[0049] (In the above general formula [4], R 1 , R 2 , e, f and W are the same as in equation [1].)
[0050] [ka]
[0051] [In formula [2], R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 and R18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of groups, they may be the same or different, g is an integer from 1 to 10, and h is an integer from 4 to 7.
[0052] Examples of the dihydric phenol include 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxy-3,3'-biphenyl)propane, 2,2-bis(4-hydroxy- 3-isopropylphenyl)propane, 2,2-bis(3-t-butyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(3-bromo-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 1,1-bis(3-cyclohexyl-4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl) 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 4,4'-sulfonyldiphenol, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfide, 2,2'-dimethyl -4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, 2,2'-diphenyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfide, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,Examples of the cyclohexane derivatives include 4-bis(4-hydroxyphenyl)cyclohexane, 1,3-bis(4-hydroxyphenyl)cyclohexane, 4,8-bis(4-hydroxyphenyl)tricyclo[5.2.1.02,6]decane, 4,4'-(1,3-adamantanediyl)diphenol, and 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane.
[0053] Among these, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene are preferred, and 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane (BPZ), 4,4'-sulfonyldiphenol, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are particularly preferred. Among them, 2,2-bis(4-hydroxyphenyl)propane is the most suitable, which can give a polycarbonate resin having excellent transparency, strength, and durability. These may be used alone or in combination of two or more kinds.
[0054] The A component in the present invention is a mixture of a polycarbonate-polydiorganosiloxane copolymer resin (A-1 component) or A-1 component and a polycarbonate resin (A-2 component) other than the A-1 component, which comprises a repeating unit represented by the above general formula [1]. The content of the A-1 component in 100 parts by weight of the A component is preferably 5 to 100 parts by weight, more preferably 20 to 100 parts by weight, and even more preferably 50 to 100 parts by weight. If the A-1 component is less than this preferred range, impact resistance may not be sufficiently exhibited.
[0055] The content of the polydiorganosiloxane block represented by the above general formula [3] in the present invention is preferably 0.5 to 20.0% by weight, more preferably 0.8 to 15.0% by weight, and even more preferably 1.0 to 9.0% by weight, based on the total weight of component A. If the content is below the lower limit of this preferred range, transparency and impact resistance may not be fully exhibited, while if the content exceeds the upper limit of this preferred range, impact resistance, mechanical properties, and heat resistance may decrease.
[0056] The viscosity average molecular weight of component A is preferably 11,000 to 30,000, and more preferably 13,000 to 25,000. If it is below the lower limit of this preferred range, it may be difficult to obtain practical mechanical strength in many fields, while if it exceeds the upper limit of this preferred range, the melt viscosity increases and a high molding processing temperature is required, which may lead to discoloration due to thermal degradation and deterioration of mechanical properties.
[0057] (Domain size of polydiorganosiloxane) The PC-POS copolymer of the present invention has an aggregate structure in which polydiorganosiloxane domains are dispersed in a polycarbonate polymer matrix.
[0058] In the present invention, the polydiorganosiloxane domain refers to a domain mainly composed of polydiorganosiloxane dispersed in a polycarbonate matrix, and may contain other components. As described above, the polydiorganosiloxane domain is not necessarily composed of a single component because its structure is formed by phase separation from the polycarbonate matrix.
[0059] In the polycarbonate-polydiorganosiloxane copolymer resin (A-1 component), the average size of the polydiorganosiloxane domains is preferably 5 to 15 nm, more preferably 7 to 12 nm. If it is less than the lower limit of this preferred range, transparency, impact resistance, and flame retardancy may not be fully exhibited, and if it exceeds the upper limit of this preferred range, the desired transparency may not be exhibited.
[0060] Furthermore, even if the average size of the polydiorganosiloxane domain is within a suitable range, if the normalized variance exceeds 25%, good and stable transparency may not be exhibited. The normalized variance of the polydiorganosiloxane domain size is more preferably 23% or less, and even more preferably 20% or less. The lower limit of the normalized variance is preferably 7% or more, and more preferably 10% or more, in practical terms. By having such a suitable average domain size and its normalized variance, a polycarbonate-polydiorganosiloxane copolymer resin and a molded article thereof that are excellent in both transparency, impact resistance, and flame retardancy may be provided.
[0061] The polycarbonate-polydiorganosiloxane copolymer resin molded product of the present invention is The average domain size and normalized dispersion of diorganosiloxane domains are evaluated by small angle X-ray scattering (SAXS). Small angle X-ray scattering is a method to measure diffuse scattering and diffraction that occurs in the small angle range where the scattering angle (2θ) is less than 10°. In this small angle X-ray scattering method, if there are regions with different electron densities of about 1 to 100 nm in a substance, the diffuse scattering of X-rays is measured due to the difference in electron density. The particle size of the object to be measured is calculated based on this scattering angle and scattering intensity. In the case of polycarbonate-polydiorganosiloxane copolymer resin, which has an aggregate structure in which polydiorganosiloxane domains are dispersed in the polycarbonate polymer matrix, the difference in electron density between the polycarbonate matrix and the polydiorganosiloxane domains causes diffuse scattering of X-rays. The scattering intensity I at each scattering angle (2θ) in the range of scattering angles (2θ) less than 10° is measured to measure the small-angle X-ray scattering profile, and assuming that the polydiorganosiloxane domains are spherical domains and that there is variation in particle size distribution, a simulation is performed using commercially available analysis software from a tentative particle size and a tentative particle size distribution model to determine the average size and particle size distribution (normalized variance) of the polydiorganosiloxane domains. The small-angle X-ray scattering method makes it possible to accurately, easily, and reproducibly measure the average size and particle size distribution of the polydiorganosiloxane domains dispersed in a polycarbonate polymer matrix, which cannot be accurately measured by observation with a transmission electron microscope.
[0062] The average domain size means the number average of the individual domain sizes. The normalized variance means a parameter that normalizes the spread of the particle size distribution by the average size. Specifically, it is a value that normalizes the variance of the polydiorganosiloxane domain size by the average domain size, and is expressed by the following formula (1).
[0063]
number
[0064] In the above formula (1), δ is the standard deviation of the polydiorganosiloxane domain size, D av is the average domain size.
[0065] The terms "average domain size" and "normalized variance" used in the present invention refer to measurements obtained by measuring a molded product having a thickness of 1.0 mm formed by injection molding using the above-mentioned small angle X-ray scattering method. Note that the analysis was performed using an isolated particle model that does not take into account interparticle interactions (interparticle interference).
[0066] (Polydiorganosiloxane) In the present invention, a polydiorganosiloxane having a specific average chain length and represented by the following general formula [5], hydroxyaryl-terminated polydiorganosiloxane (II), is used as a raw material.
[0067] [ka]
[0068] [In formula [5], R 3 , R 4 , R 5 , R 6 , R 7 and R 8 each independently represents a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number of 30 to 50. X is a divalent aliphatic group having 2 to 8 carbon atoms.
[0069] The average chain length p+q is 30 to 50, and preferably 30 to 45. If it is less than the lower limit of this preferred range, a sufficient effect of improving impact resistance cannot be obtained, and if it exceeds the upper limit of this preferred range, excellent transparency may not be achieved.
[0070] As the hydroxyaryl-terminated polydiorganosiloxane (II) represented by the general formula [5], for example, the following compounds are preferably used.
[0071] [ka]
[0072] Hydroxyaryl-terminated polydiorganosiloxane (II) is a phenol having an olefinic unsaturated carbon-carbon bond, and is easily produced by subjecting vinylphenol, 2-allylphenol, isopropenylphenol, or 2-methoxy-4-allylphenol to a hydrosilylation reaction at the end of a polysiloxane chain having a predetermined degree of polymerization. Among these, (2-allylphenol)-terminated polydiorganosiloxane and (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane are preferred, and (2-allylphenol)-terminated polydimethylsiloxane and (2-methoxy-4-allylphenol)-terminated polydimethylsiloxane are particularly preferred.
[0073] In the present invention, the hydroxyaryl-terminated polydiorganosiloxane (II) may be used alone or in combination of two or more kinds.
[0074] In addition, comonomers other than the dihydric phenol (I) and hydroxyaryl-terminated polydiorganosiloxane (II) can be used in an amount of up to 10% by weight based on the total weight of the copolymer, provided that the use does not interfere with the production process of the present invention.
[0075] <Production method of polycarbonate-polydiorganosiloxane copolymer resin> The PC-POS copolymer of the present invention is prepared by preliminarily dissolving the copolymer in a water-insoluble organic solvent. A mixed solution containing an oligomer having a terminal chloroformate group is prepared by reacting a dihydric phenol (I) with a carbonate-forming compound in a mixed solution with an aqueous alkali solution.
[0076] In producing an oligomer of the dihydric phenol (I), the entire amount of the dihydric phenol (I) used in the method of the present invention may be converted into an oligomer at once, or a part of it may be added as a post-added monomer as a reaction raw material to the interfacial polycondensation reaction in the latter stage. The post-added monomer is added to quickly advance the polycondensation reaction in the latter stage, and there is no need to add it if it is not necessary.
[0077] The method of this oligomer formation reaction is not particularly limited, but it is usually preferable to carry out the reaction in a solvent in the presence of an acid binder.
[0078] The proportion of the carbonate ester-forming compound used may be appropriately adjusted in consideration of the stoichiometric ratio (equivalent) of the reaction. When a gaseous carbonate ester-forming compound such as phosgene is used, it is preferable to employ a method of blowing the gaseous compound into the reaction system.
[0079] As the acid binder, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide, an alkali metal carbonate such as sodium carbonate or potassium carbonate, an organic base such as pyridine, or a mixture thereof can be used. The proportion of the acid binder used can be appropriately determined in consideration of the stoichiometric ratio (equivalent) of the reaction, as described above. Specifically, it is preferable to use 2 equivalents or a slightly excess amount of the acid binder relative to the number of moles of the dihydric phenol (I) used to form the oligomer (usually 1 mole corresponds to 2 equivalents).
[0080] As the solvent, a solvent inert to various reactions, such as those used in the production of known polycarbonates, may be used alone or as a mixed solvent. Representative examples include hydrocarbon solvents such as xylene, and halogenated hydrocarbon solvents such as methylene chloride and chlorobenzene. In particular, halogenated hydrocarbon solvents such as methylene chloride are preferably used.
[0081] The reaction pressure for oligomer formation is not particularly limited, and may be normal pressure, elevated pressure, or reduced pressure, but it is usually advantageous to carry out the reaction under normal pressure. The reaction temperature is selected from the range of -20 to 50°C, and in many cases, since heat is generated during polymerization, it is desirable to cool the reaction with water or ice. The reaction time depends on other conditions and cannot be specified in general, but is usually carried out for 0.2 to 10 hours.
[0082] The pH range of the oligomer formation reaction is similar to that of known interfacial reactions, and the pH is always adjusted to 10 or higher.
[0083] In the present invention, after obtaining a mixed solution containing an oligomer of dihydric phenol (I) having terminal chloroformate groups in this manner, the hydroxyaryl-terminated polydiorganosiloxane (II) is added to the dihydric phenol (I) while stirring the mixed solution, and the hydroxyaryl-terminated polydiorganosiloxane (II) and the oligomer are subjected to interfacial polycondensation to obtain a polycarbonate-polydiorganosiloxane copolymer resin.
[0084] In carrying out the interfacial polycondensation reaction, an acid binder may be appropriately added in consideration of the stoichiometric ratio (equivalent) of the reaction. For example, alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkali metal carbonates such as sodium carbonate and potassium carbonate, organic bases such as pyridine, or mixtures thereof, are used as the acid binder. Specifically, when the hydroxyaryl-terminated polydiorganosiloxane (II) used or a part of the dihydric phenol (I) as described above is added to this reaction stage as a post-added monomer, it is preferable to use 2 equivalents or more of alkali relative to the total mole number of the post-added dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) (usually 1 mole corresponds to 2 equivalents).
[0085] The polycondensation by the interfacial polycondensation reaction between the oligomer of the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) is carried out by vigorously stirring the above mixture.
[0086] In such a polymerization reaction, a terminal terminator or a molecular weight regulator is usually used. Examples of the terminal terminator include compounds having a monovalent phenolic hydroxyl group, such as ordinary phenol, p-tert-butylphenol, p-cumylphenol, tribromophenol, and the like, as well as long-chain alkylphenols, aliphatic carboxylic acid chlorides, aliphatic carboxylic acids, hydroxybenzoic acid alkyl esters, hydroxyphenyl alkyl acid esters, and alkyl ether phenols. The amount of the terminal terminator is preferably 100 to 0.5 mol, more preferably 50 to 2 mol, based on 100 mol of all dihydric phenol compounds used. It is of course possible to use two or more of the above terminal terminators in combination.
[0087] To accelerate the polycondensation reaction, a catalyst such as a tertiary amine, such as triethylamine, or a quaternary ammonium salt may be added.
[0088] The reaction time of the polymerization reaction needs to be relatively long in order to reduce the amount of unreacted polydiorganosiloxane components, and is preferably 30 minutes or more, more preferably 50 minutes or more. On the other hand, since the stirring of the reaction solution for a long period of time may cause precipitation of the polymer, the reaction time of the polymerization reaction is preferably 180 minutes or less, more preferably 90 minutes or less.
[0089] If desired, a small amount of an antioxidant such as sodium sulfite or hydrosulfide may be added.
[0090] The polycarbonate resin composition of the present invention can be made into a branched polycarbonate by using a branching agent in combination with the above-mentioned dihydric phenol compound. Examples of the trifunctional or higher polyfunctional aromatic compounds used in such branched polycarbonate resins include phloroglucin, phloroglucide, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 4-{4-[1,1-bis(4- Examples of the trisphenols include trisphenols such as 1,4-dimethylbenzylphenol, tetra(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and acid chlorides thereof. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred.
[0091] The reaction pressure may be reduced, normal, or increased, but is usually preferably normal pressure or the reaction system's own pressure. The reaction temperature is selected from the range of -20 to 50°C, and in many cases, since heat is generated during polymerization, it is desirable to cool the reaction system with water or ice. The reaction time varies depending on other conditions such as the reaction temperature and cannot be generally specified, but is usually carried out for 0.5 to 10 hours.
[0092] In some cases, the obtained polycarbonate copolymer resin is subjected to a suitable physical treatment (mixing, fractionation, etc.) and / or chemical treatment (polymer reaction, crosslinking treatment, partial decomposition treatment, etc.) to obtain a desired reduced viscosity [η SP It can also be obtained as a polycarbonate copolymer resin of formula [1 / c].
[0093] The resulting reaction product (crude product) can be subjected to various post-treatments such as known separation and purification methods to recover a polycarbonate-polydiorganosiloxane copolymer resin of a desired purity (degree of purification).
[0094] (Component B: Silver-based antibacterial agent supported on glass so that silver ions are eluted) The resin composition of the present invention contains, as component B, a silver-based glass antibacterial agent supported on glass so that silver ions are eluted. In particular, it is preferable that the composition contains silver oxide, phosphorus oxide, and zinc oxide, has excellent transparency as a composition, and has a polyhedral shape. Excellent transparency is essential for maintaining the transparency of the resin composition when mixed and dispersed in a transparent resin, and when the shape is polyhedral, it is easy to disperse uniformly in the resin and is easy to be oriented in a certain direction during molding, which suppresses light scattering, making it suitable for expressing good transparency of the resin composition.
[0095] Such a silver-based glass antibacterial agent preferably contains 0.2-5 wt% Ag2O, 50-55 wt% P2O5, 40-50 wt% ZnO, and 0.1-15 wt% B2O3, and more preferably contains 0.1-15 wt% CaO relative to the total amount, and the weight ratio of CaO to ZnO (ZnO / CaO) is within the range of 1.1 to 15. When the contents of these components are within the above-mentioned ranges, a silver-based glass antibacterial agent that is excellent in transparency and mechanical properties and stably releases silver ions, which is suitable as a component constituting the transparent antibacterial resin composition of the present invention, can be obtained.
[0096] Other factors influencing the transparency of the resin composition due to the inclusion of a silver-based glass antibacterial agent include the average particle size (D50) and the refractive index (the difference in the refractive index from the resin matrix). The average particle size (D50) of such a silver-based glass antibacterial agent measured by a laser diffraction / scattering method is preferably 1 to 30 μm, more preferably 3 to 20 μm, and even more preferably 7 to 15 μm. If the average particle size (D50) is less than 1 μm, the surface appearance efficiency on the molded article may decrease, making it difficult to express antibacterial properties, and the content may need to be increased, or light scattering may occur easily, leading to a decrease in transparency. On the other hand, if the average particle size (D50) exceeds 30 μm, the surface roughness of the molded article may occur, causing a deterioration in appearance, or the impact resistance may decrease. In addition, the smaller the difference in the refractive index of such a silver-based glass antibacterial agent with the resin matrix, the more the transparency of the resin composition is improved, so the difference in the refractive index is most preferably 0, but due to the characteristics of the refractive index inherent to the substance, such as the Abbe number and anisotropy, it is practically difficult to achieve this. Therefore, the refractive index difference is preferably 0.1 or less, more preferably 0.05 or less, and even more preferably 0.03 or less. An example of the silver-based glass antibacterial agent in the present invention is Zeomic KM10D (product name) manufactured by Sinanen Zeomic Co., Ltd., which is easily available as a commercial product.
[0097] The content of component B is 0.3 to 5 parts by weight, preferably 0.3 to 3 parts by weight, and more preferably 0.3 to 1 part by weight, relative to 100 parts by weight of component A. If the content of component B is less than 0.3 parts by weight, antibacterial properties are not expressed, whereas if it exceeds 5 parts by weight, transparency is impaired and impact resistance is significantly reduced.
[0098] (Component C: phosphorus stabilizer) The resin composition of the present invention may contain a phosphorus-based stabilizer as component C to the extent that it does not promote hydrolysis. Such a phosphorus-based stabilizer improves the thermal stability during production or molding processing, and improves mechanical properties, color, and molding stability. Examples of the acid include phosphorous acid, phosphoric acid, phosphonous acid, phosphonic acid and their esters, and tertiary phosphines.
[0099] Specific examples of the phosphite compound include triphenyl phosphite, tris(nonylphenyl)phosphite, tridecyl phosphite, trioctyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, tris(diethylphenyl)phosphite, tris(di-iso-propylphenyl)phosphite, and tris(di-n-butylphenyl)phosphite. pentaerythritol diphosphite, tris(2,4-di-tert-butylphenyl)phosphite, tris(2,6-di-tert-butylphenyl)phosphite, distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-ethylphenyl)pentaerythritol diphosphite, phenyl bisphenol A pentaerythritol diphosphite, bis(nonylphenyl)pentaerythritol diphosphite, dicyclohexyl pentaerythritol diphosphite, and the like.
[0100] Other phosphite compounds that react with dihydric phenols to form a cyclic structure can also be used, such as 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2,4-di-tert-butylphenyl)phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, 2,2'-methylenebis(4-methyl-6-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, and 2,2'-ethylidenebis(4-methyl-6-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite.
[0101] Examples of the phosphate compound include tributyl phosphate, trimethyl phosphate, tricresyl phosphate, triphenyl phosphate, trichlorophenyl phosphate, triethyl phosphate, diphenyl cresyl phosphate, diphenyl monoorthoxenyl phosphate, tributoxyethyl phosphate, dibutyl phosphate, dioctyl phosphate, diisopropyl phosphate, etc. Preferred are triphenyl phosphate and trimethyl phosphate.
[0102] The phosphonite compounds include tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, and tetrakis(2 ,6-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, bis(2,4-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, bis(2,4-di-tert-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-n-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, bis(2,6-di-tert-butylphenyl)-3-phenyl-phenylphosphonite, etc. Among them, tetrakis(di-tert-butylphenyl)-biphenylene diphosphonite, bis(di-tert-butylphenyl)-phenyl-phenylphosphonite, etc. are particularly preferred. Nylphosphonite is preferred, and tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphonite and bis(2,4-di-tert-butylphenyl)-phenyl-phenylphosphonite are more preferred. Such phosphonite compounds can be used in combination with the above-mentioned phosphite compounds having an aryl group substituted with two or more alkyl groups, and are therefore preferred.
[0103] Examples of the phosphonate compound include dimethyl benzenephosphonate, diethyl benzenephosphonate, and dipropyl benzenephosphonate.
[0104] Examples of tertiary phosphines include triethylphosphine, tripropylphosphine, tributylphosphine, trioctylphosphine, triamylphosphine, dimethylphenylphosphine, dibutylphenylphosphine, diphenylmethylphosphine, diphenyloctylphosphine, triphenylphosphine, tri-p-tolylphosphine, trinaphthylphosphine, and diphenylbenzylphosphine. A particularly preferred tertiary phosphine is triphenylphosphine.
[0105] The phosphorus-based stabilizer may be used alone or in combination with two or more kinds. Among the phosphorus-based stabilizers, it is preferable to use a phosphite compound and a phosphonite compound in combination.
[0106] The content of the C component is preferably 0.001 to 0.5 parts by weight, more preferably 0.005 to 0.3 parts by weight, and even more preferably 0.01 to 0.1 parts by weight, relative to 100 parts by weight of the A component.
[0107] (Component D: Release agent) The resin composition of the present invention may contain a mold release agent as component D in order to improve mold releasability during molding and reduce distortion of molded products, within the scope of the present invention.
[0108] As such a mold release agent, a known one can be used. For example, a saturated fatty acid ester, an unsaturated fatty acid ester, a polyolefin wax (polyethylene wax, 1-alkene polymer, etc., modified with a functional group-containing compound such as an acid modification can also be used), a silicone compound (silicone oil, organosiloxane, etc.), a fluorine compound (fluorine oil represented by polyfluoroalkyl ether, etc.), a paraffin wax, a beeswax, etc. can be mentioned. Among them, a fatty acid ester can be mentioned as a preferable mold release agent.
[0109] Such fatty acid esters are esters of aliphatic alcohols and aliphatic carboxylic acids. Such aliphatic alcohols may be monohydric alcohols or polyhydric alcohols having dihydric or higher valences, and the number of carbon atoms is preferably in the range of 3 to 32, more preferably in the range of 5 to 30. Examples of such monohydric alcohols include dodecanol, tetradecanol, hexadecanol, octadecanol, eicosanol, tetracosanol, ceryl alcohol, and triacontanol. Examples of such polyhydric alcohols include pentaerythritol, dipentaerythritol, tripentaerythritol, polyglycerol (triglycerol to hexaglycerol), ditrimethylolpropane, xylitol, sorbitol, and mannitol. In the fatty acid ester of the present invention, polyhydric alcohols are more preferable.
[0110] On the other hand, the aliphatic carboxylic acid preferably has 3 to 32 carbon atoms, and particularly preferably has 10 to 22 carbon atoms. Examples of the aliphatic carboxylic acid include saturated aliphatic carboxylic acids such as decanoic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid (palmitic acid), heptadecanoic acid, octadecanoic acid (stearic acid), nonadecanoic acid, behenic acid, icosanoic acid, and docosanoic acid, and unsaturated aliphatic carboxylic acids such as palmitoleic acid, oleic acid, linoleic acid, linolenic acid, eicosenoic acid, eicosapentaenoic acid, and cetoleic acid. Among the above, the aliphatic carboxylic acid is preferably one having 14 to 20 carbon atoms. Among them, saturated aliphatic carboxylic acids are more preferable. In particular, stearic acid and palmitic acid are even more preferable.
[0111] The above-mentioned aliphatic carboxylic acids such as stearic acid and palmitic acid are usually produced from natural oils and fats such as animal oils and fats such as beef tallow and lard, and vegetable oils and fats such as palm oil and sunflower oil, and therefore these aliphatic carboxylic acids are usually mixtures containing other carboxylic acid components with different numbers of carbon atoms. Therefore, in the production of the fatty acid ester of the present invention, aliphatic carboxylic acids produced from such natural oils and fats and in the form of a mixture containing other carboxylic acid components, particularly stearic acid and palmitic acid, are preferably used.
[0112] The fatty acid ester may be either a partial ester or a full ester (full ester). However, since partial esters usually have a high hydroxyl value and tend to induce decomposition of the resin at high temperatures, full esters are more preferred. The acid value of such fatty acid esters is preferably 20 or less, more preferably 4 to 20, and even more preferably 4 to 12, from the viewpoint of thermal stability. The acid value can be substantially 0. In addition, the hydroxyl value of such fatty acid esters is preferably 0.1 to 30, and the iodine value of such fatty acid esters is preferably 10 or less. The iodine value can be substantially 0. These properties can be determined by the method specified in JIS K 0070.
[0113] The above releasing agents may be used alone or in combination of two or more.
[0114] The content of the D component is preferably from 0.01 to 2 parts by weight, more preferably from 0.05 to 1.5 parts by weight, and even more preferably from 0.1 to 1 part by weight, relative to 100 parts by weight of the A component.
[0115] (Component E: UV absorber) The resin composition of the present invention may contain an ultraviolet absorber as component E for the purpose of imparting light resistance. Examples of ultraviolet absorbers include benzophenone-based ultraviolet absorbers, cyclic iminoester-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, and triazine-based ultraviolet absorbers. Among these, benzotriazole-based ultraviolet absorbers and triazine-based ultraviolet absorbers are preferred.
[0116] Benzotriazole-based ultraviolet absorbers include 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-dicumylphenyl)phenylbenzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole, Examples of such benzotriazoles include 2-(2-hydroxy-3,5-di-tert-amylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-4-octoxyphenyl)benzotriazole, 2,2'-methylenebis(4-cumyl-6-benzotriazolephenyl), 2,2'-p-phenylenebis(1,3-benzoxazin-4-one), and 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole. Other examples include polymers having a 2-hydroxyphenyl-2H-benzotriazole skeleton, such as a copolymer of 2-(2'-hydroxy-5-methacryloxyethylphenyl)-2H-benzotriazole and a vinyl monomer copolymerizable with said monomer, and a copolymer of 2-(2'-hydroxy-5-acryloxyethylphenyl)-2H-benzotriazole and a vinyl monomer copolymerizable with said monomer.
[0117] As the triazine-based ultraviolet absorber, hydroxyphenyl triazine-based compounds such as 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-hexyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-methyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-ethyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-propyloxyphenol, and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-butyloxyphenol are preferred examples.Furthermore, compounds in which the phenyl group of the hydroxyphenyl triazine-based compounds listed above is a 2,4-dimethylphenyl group are also exemplified, such as 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hexyloxyphenol.
[0118] The above ultraviolet absorbents may be used alone or in combination of two or more kinds.
[0119] The content of the E component is preferably substantially 0 parts by weight when light resistance is not required and / or when considering suppression of deterioration of the mechanical properties (especially impact resistance, etc.) of the resin composition. However, since light resistance is required in many applications, when light resistance is to be imparted, the content of the E component is preferably 1 part by weight or less, more preferably 0.5 parts by weight or less, and even more preferably 0.3 parts by weight or less, relative to 100 parts by weight of the A component. When the content of the E component exceeds 1 part by weight, not only the mechanical properties of the resin composition are significantly decreased as described above, but also coloring due to light absorption by the ultraviolet absorber and transparency may be impaired.
[0120] (Other additives) The resin composition of the present invention may contain various known additives depending on the application and necessity, such as flame retardants, fluorine-containing anti-dripping agents, plasticizers, impact modifiers, antistatic agents, light diffusing agents, fillers (titanium oxide, talc, mica, glass fiber, carbon fiber, etc.), fluorescent whitening agents, dyes and pigments, etc.
[0121] In particular, polycarbonate resins are known as resins having self-extinguishing properties and excellent flame retardancy, and because of this characteristic, there are many cases where improvement in flame retardancy is required. Therefore, as additives related to the improvement of such flame retardancy, (i) flame retardants and (ii) fluorine-containing drip inhibitors will be described below.
[0122] (i) Flame retardants As flame retardants, various compounds known as flame retardants for thermoplastic resins, particularly aromatic polycarbonate resins, can be used, but more preferred are (i) organometallic salt-based flame retardants (e.g., organic sulfonic acid alkali (earth) metal salts, boric acid metal salt-based flame retardants, and stannic acid metal salt-based flame retardants, etc., (ii) organophosphorus-based flame retardants (e.g., monophosphate compounds, phosphate oligomer compounds, phosphonate oligomer compounds, phosphonitrile oligomer compounds, and phosphonic acid amide compounds, etc.), and (iii) silicone-based flame retardants consisting of silicone compounds. The incorporation of compounds used as flame retardants not only improves flame retardancy, but also brings about improvements in, for example, antistatic properties, fluidity, rigidity, and thermal stability based on the properties of each compound.
[0123] (Organometallic salt flame retardants) The organic metal salt-based flame retardant is advantageous in that it maintains heat resistance to a large extent. The organic metal salt flame retardant advantageously used is an alkali (earth) metal salt of sulfonic acid. Among them, an alkali (earth) metal salt of fluorine-substituted organic sulfonic acid is preferable, and an alkali (earth) metal salt of sulfonic acid having a perfluoroalkyl group is more preferable. Here, the carbon number of the perfluoroalkyl group is preferably 1 to 18, more preferably 1 to 10, and further preferably 1 to 8.
[0124] The metal constituting the metal ion of the fluorine-substituted organic sulfonic acid alkali (earth) metal salt is an alkali metal or an alkaline earth metal, and examples of the alkali metal include lithium, sodium, potassium, rubidium, and cesium, and examples of the alkaline earth metal include beryllium, magnesium, calcium, strontium, and barium. More preferably, it is an alkali metal. Therefore, a suitable organic metal salt-based flame retardant is a perfluoroalkylsulfonic acid alkali metal salt. Among such alkali metals, rubidium and cesium are suitable when a higher transparency is required, but they are not versatile and difficult to purify, so that they may end up being disadvantageous in terms of cost. On the other hand, although they are advantageous in terms of cost and flame retardancy, lithium and sodium may conversely be disadvantageous in terms of transparency. Taking these into consideration, the alkali metals in the perfluoroalkylsulfonic acid alkali metal salt can be used differently, but in all respects, the most suitable is a perfluoroalkylsulfonic acid potassium salt, which has an excellent balance of properties. Such a potassium salt can also be used in combination with a perfluoroalkylsulfonic acid alkali metal salt made of another alkali metal.
[0125] Examples of such perfluoroalkylsulfonic acid alkali metal salt include potassium trifluoromethanesulfonate, potassium perfluorobutanesulfonate, potassium perfluorohexanesulfonate, potassium perfluorooctane sulfonate, sodium pentafluoroethanesulfonate, sodium perfluorobutanesulfonate, sodium perfluorooctane sulfonate, lithium trifluoromethanesulfonate, lithium perfluorobutanesulfonate, lithium perfluoroheptanesulfonate, cesium trifluoromethanesulfonate, cesium perfluorobutanesulfonate, cesium perfluorooctane sulfonate, cesium perfluorohexanesulfonate, rubidium perfluorobutanesulfonate, and rubidium perfluorohexanesulfonate, and the like, and these can be used alone or in combination of two or more.Among these, potassium perfluorobutanesulfonate is particularly preferred.
[0126] The above-mentioned organometallic salt flame retardant has a fluoride ion content measured by ion chromatography of preferably 50 ppm or less, more preferably 20 ppm or less, and even more preferably 10 ppm or less. The lower the fluoride ion content, the better the flame retardancy and light resistance. The lower limit of the fluoride ion content can be substantially 0, but in terms of the balance between the refining man-hours and the effect, a practical value of about 0.2 ppm is preferable. A perfluoroalkylsulfonic acid alkali metal salt having such a fluoride ion content is refined, for example, as follows. A perfluoroalkylsulfonic acid alkali metal salt is dissolved in ion-exchanged water in an amount 2 to 10 times the weight of the metal salt at a temperature in the range of 40 to 90°C (more preferably 60 to 85°C). The alkali metal salt of perfluoroalkylsulfonic acid is produced by a method of neutralizing perfluoroalkylsulfonic acid with an alkali metal carbonate or hydroxide, or a method of neutralizing perfluoroalkylsulfonyl fluoride with an alkali metal carbonate or hydroxide (preferably the latter method). The ion-exchanged water is particularly preferably water having an electric resistance value of 18 MΩ·cm or more. The liquid in which the metal salt is dissolved is stirred at the above temperature for 0.1 to 3 hours, more preferably for 0.5 to 2.5 hours. Thereafter, the liquid is cooled to a range of 0 to 40°C, more preferably 10 to 35°C. Crystals are precipitated by cooling. The precipitated crystals are taken out by filtration. In this way, a suitable purified alkali metal salt of perfluoroalkylsulfonic acid is produced.
[0127] When a fluorine-substituted organic sulfonic acid alkali (earth) metal salt is contained as a flame retardant, the content is preferably 0.01 to 1.0 part by weight, more preferably 0.05 to 0.8 part by weight, and even more preferably 0.08 to 0.6 part by weight, relative to 100 parts by weight of component A. Within such a preferred range, the effects (e.g., flame retardancy, antistatic properties, etc.) expected from the inclusion of a fluorine-substituted organic sulfonic acid alkali (earth) metal salt may be exhibited.
[0128] As the organic metal salt-based flame retardant other than the fluorine-substituted organic sulfonic acid alkali (earth) metal salt, a metal salt of an organic sulfonic acid that does not contain a fluorine atom is suitable. Examples of such metal salts include an alkali metal salt of an aliphatic sulfonic acid, an alkaline earth metal salt of an aliphatic sulfonic acid, an alkali metal salt of an aromatic sulfonic acid, and an alkaline earth metal salt of an aromatic sulfonic acid (none of which contain a fluorine atom).
[0129] Preferred examples of the aliphatic sulfonic acid metal salt include alkylsulfonic acid alkali (earth) metal salts, which can be used alone or in combination of two or more (herein, the term "alkali (earth) metal salt" is used to mean both alkali metal salts and alkaline earth metal salts). Preferred examples of the alkane sulfonic acid used in such alkylsulfonic acid alkali (earth) metal salts include methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, butanesulfonic acid, methylbutanesulfonic acid, hexanesulfonic acid, heptanesulfonic acid, octanesulfonic acid, etc., which can be used alone or in combination of two or more.
[0130] The aromatic sulfonic acid used in the alkali (earth) metal salt of aromatic sulfonate may be at least one acid selected from the group consisting of monomeric or polymeric aromatic sulfide sulfonic acids, aromatic carboxylic acids and ester sulfonic acids, monomeric or polymeric aromatic ether sulfonic acids, aromatic sulfonate sulfonic acids, monomeric or polymeric aromatic sulfonic acids, monomeric or polymeric aromatic sulfone sulfonic acids, aromatic ketone sulfonic acids, heterocyclic sulfonic acids, aromatic sulfoxide sulfonic acids, and condensates of aromatic sulfonic acids with methylene bonds, and these may be used alone or in combination of two or more kinds.
[0131] Specific examples of the aromatic sulfonic acid alkali (earth) metal salts include disodium diphenyl sulfide-4,4'-disulfonate, dipotassium diphenyl sulfide-4,4'-disulfonate, potassium 5-sulfoisophthalate, sodium 5-sulfoisophthalate, polysodium polyethylene terephthalate polysulfonate, calcium 1-methoxynaphthalene-4-sulfonate, disodium 4-dodecylphenyl ether disulfonate, polysodium poly(2,6-dimethylphenylene oxide) polysulfonate, polysodium poly(1,3-phenylene oxide) polysulfonate, polysodium poly(1,4-phenylene oxide) polysulfonate, polypotassium poly(2,6-diphenylphenylene oxide) polysulfonate, lithium poly(2-fluoro-6-butylphenylene oxide) polysulfonate, potassium sulfonate of benzenesulfonate, sodium benzenesulfonate, and sodium benzenesulfonate. Examples of suitable sulfonates include thoronium, magnesium benzenesulfonate, dipotassium p-benzenedisulfonate, dipotassium naphthalene-2,6-disulfonate, calcium biphenyl-3,3'-disulfonate, sodium diphenylsulfone-3-sulfonate, potassium diphenylsulfone-3-sulfonate, dipotassium diphenylsulfone-3,3'-disulfonate, dipotassium diphenylsulfone-3,4'-disulfonate, sodium α,α,α-trifluoroacetophenone-4-sulfonate, dipotassium benzophenone-3,3'-disulfonate, disodium thiophene-2,5-disulfonate, dipotassium thiophene-2,5-disulfonate, calcium thiophene-2,5-disulfonate, sodium benzothiophenesulfonate, potassium diphenylsulfoxide-4-sulfonate, a formalin condensate of sodium naphthalenesulfonate, and a formalin condensate of sodium anthracenesulfonate.
[0132] Among the metal salts of fluorine-free organic sulfonic acids, aromatic sulfonic acid alkali (earth) metal salts are preferred, and potassium salts are particularly preferred. When such aromatic sulfonic acid alkali (earth) metal salts are contained as flame retardants, the content is preferably 0.01 to 1 part by weight, more preferably 0.05 to 0.8 parts by weight, and even more preferably 0.08 to 0.6 parts by weight, per 100 parts by weight of component A.
[0133] (Organophosphorus flame retardants) As the organic phosphorus flame retardant in the present invention, a phosphate compound, particularly an aryl phosphate compound, is preferred. Such a phosphate compound is effective in improving flame retardancy, and has a plasticizing effect, so that it is advantageous in that it can improve the molding processability of the resin composition of the present invention, although it reduces heat resistance. As such a phosphate compound, various phosphate compounds known as flame retardants can be used, but more preferably, one or more phosphate compounds represented by the following general formula [6] can be mentioned.
[0134] [ka]
[0135] [In formula [6], Y is a dihydric phenol residue derived from a dihydroxy compound selected from the group consisting of hydroquinone, resorcinol, bis(4-hydroxydiphenyl)methane, bisphenol A, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3-methylcyclohexane, dihydroxydiphenyl, dihydroxynaphthalene, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)ketone, and bis(4-hydroxyphenyl)sulfide; g, h, i, and j are each independently 0 or 1; n is an integer of 0 to 5, or in the case of a mixture of phosphate esters having different n's, is an average value thereof; R 21 , R 22 , R23 , and R 24 are each independently a monohydric phenol residue derived from an aryl group selected from the group consisting of phenol, cresol, xylenol, isopropylphenol, butylphenol, and p-cumylphenol.
[0136] The phosphate compound of the above formula [6] may be a mixture of compounds having different n numbers. In the case of such a mixture, the average n number is preferably 0.5 to 1.5, more preferably 0.8 to 1.2, even more preferably 0.95 to 1.15, and particularly preferably 1 to 1.14.
[0137] Preferred specific examples of the dihydric phenol from which Y in the above formula [6] is derived include resorcinol, bisphenol A, and dihydroxydiphenyl, and among these, resorcinol and bisphenol A are preferred.
[0138] R in the above formula [6] 21 , R 22 , R 23 , and R 24 Preferred specific examples of the monohydric phenol from which the above is derived include phenol, cresol, xylenol, and 2,6-dimethylphenol, and among these, phenol and 2,6-dimethylphenol are preferred.
[0139] Specific examples of the phosphate compound of the above formula [6] include monophosphate compounds such as triphenyl phosphate and tri(2,6-xylyl)phosphate, as well as phosphate oligomers based on resorcinol bis(di(2,6-xylyl)phosphate), phosphate oligomers based on 4,4-dihydroxydiphenyl bis(diphenyl phosphate), and phosphoric ester oligomers based on bisphenol A bis(diphenyl phosphate). Of these, phosphate oligomers based on resorcinol bis(di(2,6-xylyl)phosphate), phosphate oligomers based on 4,4-dihydroxydiphenyl bis(diphenyl phosphate), and phosphoric ester oligomers based on bisphenol A bis(diphenyl phosphate) are preferred.
[0140] Another example of an organic phosphorus-based flame retardant is phosphazene. Phosphazene contains phosphorus and nitrogen atoms in the molecule, which can impart flame retardancy to a resin composition. There are no particular limitations on the phosphazene, so long as it does not contain halogen atoms and has a phosphazene structure in the molecule. The phosphazene structure here refers to a structure represented by the formula: -P(R)=N- [wherein R is an organic group]. The phosphazene compound is represented by the general formulas [7] and [8].
[0141] [ka]
[0142] [ka]
[0143] (In the above general formulas [7] and [8], R 25 , R 26 , R 27 and R 28 represents an organic group that does not contain hydrogen, a hydroxyl group, an amino group, or a halogen atom, and n represents an integer of 3 to 10.
[0144] In the above formulas [7] and [8], R 25 , R 26 , R 27 , and R 28 Examples of the organic group not containing a halogen atom represented by the formula (I) include an alkoxy group, a phenyl group, an amino group, and an allyl group. Among these, cyclic phenoxyphosphazenes represented by the following general formula [9] are preferred.
[0145] [ka] [In the above general formula [9], n represents an integer of 3 to 10.]
[0146] When an organic phosphorus-based flame retardant is contained as the flame retardant, the content is preferably 1 to 20 parts by weight, more preferably 2 to 15 parts by weight, and even more preferably 3 to 10 parts by weight, relative to 100 parts by weight of component A. Within such a suitable range, the effects (e.g., flame retardancy) expected from the inclusion of the organic phosphorus-based flame retardant may be exhibited without impairing transparency.
[0147] (Silicone compounds) The silicone compound in the present invention is not particularly limited as long as it can obtain the transparency that is the object of the present invention, but it is preferable that the silicone compound has an aromatic group, and more preferably has a viscosity of 300 cSt or less at 25 ° C. If the viscosity is high, the transparency of the molded product may decrease. Furthermore, in order for the silicone compound to efficiently exert a flame retardant effect, the dispersion state during the combustion process is important. Viscosity is an important factor that determines such a dispersion state. This is because when the silicone compound is too easily volatilized during the combustion process, that is, when the silicone compound has too low a viscosity, the silicone remaining in the system during combustion is thin, making it difficult to form a uniform silicone structure during combustion. From this viewpoint, the viscosity at 25 ° C. is more preferably 10 to 300 cSt, more preferably 15 to 200 cSt, and particularly preferably 20 to 170 cSt.
[0148] The aromatic group of silicone compounds is bonded to silicone atoms, which contributes to improving compatibility with polycarbonate resins and maintaining transparency, and is also advantageous in forming a carbonized film during combustion, which contributes to the expression of flame retardant effects. If the compound does not have an aromatic group, it is difficult to obtain transparency in molded products, and it tends to be difficult to obtain high levels of flame retardancy.
[0149] The silicone compound of the present invention is preferably a silicone compound containing a Si-H group. In particular, it is a silicone compound containing a Si-H group and an aromatic group in the molecule, It is more preferable to use at least one silicone compound selected from the group consisting of silicone compounds having (1) an amount of Si-H groups (Si-H amount) of 0.1 to 1.2 mol / 100 g, (2) a ratio of aromatic groups represented by the following general formula
[10] (aromatic group amount) of 10 to 70% by weight, and (3) an average degree of polymerization of 3 to 150.
[0150] [ka]
[0151] (In formula
[10] , X's each independently represent a hydrocarbon group having 1 to 20 carbon atoms which may have an OH group or a heteroatom-containing functional group. m1 represents an integer of 0 to 5. Furthermore, when m1 is 2 or more in formula
[10] , each X may be different from the others.)
[0152] More preferably, the silicone compound is at least one selected from among silicone compounds containing, as the Si-H group-containing unit, a structural unit represented by at least one of the following general formulas
[11] and
[12] .
[0153] [ka]
[0154] [ka]
[0155] (In formula
[11] and formula
[12] , Z 1 ~Z 3 each independently represents a hydrogen atom, a hydrocarbon group having 1 to 20 carbon atoms which may have a heteroatom-containing functional group, or a compound represented by the following general formula
[13] . α1 to α3 each independently represent 0 or 1. m2 represents an integer of 0 or 1 or more. Furthermore, in formula
[11] , when m2 is 2 or more, the repeating unit can be a plurality of repeating units which are different from each other.
[0156] [ka]
[0157] (In formula
[13] , Z 4 ~Z 8 Each independently represents a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms which may have a heteroatom-containing functional group. Each of α4 to α8 independently represents 0 or 1. m3 represents an integer of 0 or 1 or more. Furthermore, in the formula
[14] , when m3 is 2 or more, the repeating unit can be a plurality of repeating units which are different from each other.
[0158] More preferably, when M is a monofunctional siloxane unit, D is a difunctional siloxane unit, and T is a trifunctional siloxane unit, the silicone compound is composed of MD units or MDT units.
[0159] The structural units Z represented by the above formulas
[11] ,
[12] and
[13] 1 ~Z 8and examples of the hydrocarbon group having 1 to 20 carbon atoms which may have a heteroatom-containing functional group in X of the above formula
[10] include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and decyl groups, cycloalkyl groups such as cyclohexyl groups, alkenyl groups such as vinyl and allyl groups, aryl groups such as phenyl and tolyl groups, and aralkyl groups. Furthermore, these groups may contain various functional groups such as an epoxy group, a carboxyl group, a carboxylic anhydride group, an amino group, a mercapto group, etc. More preferred are an alkyl group, an alkenyl group, or an aryl group having 1 to 8 carbon atoms, and particularly preferred are an alkyl group having 1 to 4 carbon atoms such as a methyl group, an ethyl group, or a propyl group, a vinyl group, or a phenyl group.
[0160] In a silicone compound containing at least one of the structural units represented by the formulas
[11] and
[12] above, when the compound has a plurality of repeating units of siloxane bonds, the repeating units may be in the form of a random copolymer, a block copolymer, or a tapered copolymer.
[0161] In the present invention, for a silicone compound containing a Si-H group, the Si-H amount in the silicone compound is preferably in the range of 0.1 to 1.2 mol / 100g. When the Si-H amount is in the range of 0.1 to 1.2 mol / 100g, the formation of a silicone structure during combustion becomes easy. Moreover, the Si-H amount is more preferably 0.1 to 1.0 mol / 100g, and even more preferably 0.2 to 0.6 mol / 100g. If it is less than this preferred range, it becomes difficult to form a silicone structure, and if it exceeds this preferred range, the thermal stability of the composition decreases. Here, the silicone structure refers to a network structure formed by the reaction between silicone compounds or the reaction between a resin and a silicone.
[0162] The amount of Si-H groups referred to here refers to the number of moles of Si-H structure contained in 100g of silicone compound, which can be determined by measuring the volume of hydrogen gas generated per unit weight of silicone compound using an alkali decomposition method.For example, if 122ml of hydrogen gas is generated per 1g of silicone compound at 25°C, the amount of Si-H is calculated to be 0.5mol / 100g according to the following formula. 122×273 / (273+25)÷22400×100≒0.5
[0163] The silicone compound of the present invention has an aromatic group content of preferably 10 to 70% by weight, more preferably 15 to 60% by weight, and even more preferably 25 to 55% by weight. If the content is less than this preferred range, the silicone compound may be unevenly distributed and poorly dispersed, resulting in poor appearance. On the other hand, if the content exceeds this preferred range, the silicone compound itself has high molecular rigidity, so that it is unevenly distributed and poorly dispersed, resulting in poor appearance.
[0164] The amount of aromatic groups herein refers to the proportion of aromatic groups represented by the above-mentioned formula
[10] contained in the silicone compound, and can be calculated by the following formula. Aromatic group amount = [A / M] × 100 (weight%) Here, A and M in the above formula respectively represent the following values. A = the total molecular weight of all aromatic groups represented by the general formula
[10] contained in one molecule of the silicone compound M = molecular weight of silicone compound
[0165] Furthermore, the silicone compound used in the present invention preferably has a refractive index of 1.40 to 1.60, more preferably 1.42 to 1.59, and even more preferably 1.44 to 1.59 at 25° C. When the refractive index is within such a suitable range, the silicone compound is finely dispersed in the aromatic polycarbonate, thereby providing a resin composition with less cloudiness and good dyeability.
[0166] Furthermore, the silicone compound used in the present invention preferably has a volatilization amount of 18% or less as measured by a heat loss method at 105°C for 3 hours. More preferably, the silicone compound has a volatilization amount of 10% or less. If the volatilization amount is more than 18%, a problem occurs in that the amount of volatile matter from the resin increases when the resin composition of the present invention is extruded and pelletized, and further, the composition becomes too hot. There is a problem that a large amount of air bubbles tend to form in the molded product.
[0167] The silicone compound used may be linear or branched as long as it satisfies the above conditions, and various compounds having Si-H groups at a side chain, terminal, or branch point in the molecular structure, or at multiple sites, can be used.
[0168] Generally, the structure of a silicone compound containing Si-H groups in the molecule is composed of any combination of the four types of siloxane units shown below. M units: (CH3)3SiO 1 / 2 , H(CH3)2SiO 1 / 2 , H2(CH3)SiO 1 / 2 , (CH3)2(CH2=CH)SiO 1 / 2 , (CH3)2(C6H5)SiO 1 / 2 , (CH3)(C6H5)(CH2=CH)SiO 1 / 2 Monofunctional siloxane units such as D unit: bifunctional siloxane unit such as (CH3)2SiO, H(CH3)SiO, H2SiO, H(C6H5)SiO, (CH3)(CH2=CH)SiO, (C6H5)2SiO, etc. T units: (CH3)SiO 3 / 2 , (C3H7)SiO 3 / 2 , HSiO 3 / 2 , (CH2=CH)SiO 3 / 2 , (C6H5)SiO 3 / 2 Trifunctional siloxane units such as Q unit: tetrafunctional siloxane unit represented by SiO2
[0169] The structure of the silicone compound containing Si-H groups used in the present invention is specifically represented by the rational formula D n , T p , M m D n , M m T p , M m Q q , M m D n T p , M m D n Q q , M m T p Q q , M m D n T p Q q , D n T p , D n Q q , D n T p Q q Among these, the preferred structure of the silicone compound is M m D n , M m T p , M m D n T p , M m D n Q q and a more preferred structure is M m D n or M m D n T p It is. (The coefficients m, n, p, and q in the above rational formula are integers that represent the degree of polymerization of each siloxane unit. Furthermore, when any of m, n, p, and q is a value of 2 or more, the siloxane unit with that coefficient can be two or more types of siloxane units that have different hydrocarbon groups having 1 to 20 carbon atoms that may have a bonded hydrogen atom or a heteroatom-containing functional group.)
[0170] Here, the sum of the coefficients in each rational formula is the average degree of polymerization of the silicone compound. In the present invention, the average degree of polymerization is preferably 3 to 150, more preferably 4 to 80, and even more preferably 5 to 60. If it is less than this preferred range, the volatility of the silicone compound itself becomes high, so there is a problem that the amount of volatile matter from the resin tends to increase during processing of the resin composition containing the silicone compound. If it exceeds this preferred range, the flame retardancy and transparency of the resin composition containing the silicone compound tend to be insufficient. The above silicone compounds may be used alone or in combination of two or more.
[0171] Such a silicone compound having a Si-H bond can be produced by a conventional method. For example, according to the structure of the desired silicone compound, the corresponding organochlorosilanes are co-hydrolyzed, and the by-product hydrochloric acid and low boiling points are removed to obtain the desired product. In addition, when silicone oils, cyclic siloxanes, and alkoxysilanes having a hydrocarbon group having 1 to 20 carbon atoms, which may have a Si-H bond or an aromatic group represented by the general formula
[10] or other heteroatom-containing functional group in the molecule, are used as starting materials, and an acid catalyst such as hydrochloric acid, sulfuric acid, or methanesulfonic acid is used, and water for hydrolysis is added in some cases to proceed with the polymerization reaction, and then the acid catalyst and low boiling points used are similarly removed to obtain the desired silicone compound.
[0172] Furthermore, the silicone compound containing Si-H groups has siloxane units M and M represented by the following structural formula: H , D, D H , D φ2 , T, T φ (where M is (CH3)3SiO 1 / 2 M H :H(CH3)2SiO 1 / 2 D: (CH3)2SiOD H :H(CH3)SiOD φ2 :(C6H5)2SiT:(CH3)SiO 3 / 2 T φ :(C6H5)SiO3 / 2 ), and the average number of each siloxane unit per molecule is m and m h , d, d h , d p2 , t, t p In this case, it is preferable that all of the following relations are satisfied. 2 ≦ m+m h <= 40 0.35 ≦ d+d h +d p2 <= 148 0 ≦ t+t p <= 38 0.35 ≦ m h +d h <= 110 If the above range is not satisfied, it becomes difficult to simultaneously achieve good flame retardancy and excellent transparency in the resin composition of the present invention, and in some cases it becomes difficult to produce the silicone compound containing Si-H groups.
[0173] When a silicone compound is contained as a flame retardant, the content is preferably 0.1 to 7 parts by weight, more preferably 0.1 to 4 parts by weight, even more preferably 0.1 to 2 parts by weight, and particularly preferably 0.1 to 1 part by weight, relative to 100 parts by weight of component A. If the content exceeds this preferred range, the heat resistance of the resin may decrease and gas may be easily generated during processing, and if it is below this preferred range, flame retardancy may not be exhibited.
[0174] (ii) Fluorine-containing drip prevention agent The resin composition of the present invention may contain a fluorine-containing drip-preventing agent. By containing this fluorine-containing drip-preventing agent, good flame retardancy can be achieved without impairing the physical properties of the molded article.
[0175] Examples of the fluorine-containing drip prevention agent include fluorine-containing polymers having fibril-forming ability, and examples of such polymers include polytetrafluoroethylene, tetrafluoroethylene copolymers (e.g., tetrafluoroethylene / hexafluoropropylene copolymers, etc.), partially fluorinated polymers as shown in U.S. Patent No. 4,379,910, polycarbonate resins produced from fluorinated diphenols, etc. Among these, polytetrafluoroethylene (hereinafter sometimes referred to as PTFE) is preferred.
[0176] The molecular weight of the fibril-forming PTFE is extremely high, and it shows a tendency to bond PTFE to each other and become fibrous by external action such as shear force. The molecular weight is preferably 1 million to 10 million, more preferably 2 million to 9 million, in terms of number average molecular weight calculated from standard specific gravity. Such PTFE can be used in the form of a solid or an aqueous dispersion. In addition, such fibril-forming PTFE can be used in the form of a PTFE mixture mixed with other resins to improve dispersibility in resins and obtain better flame retardancy and mechanical properties.
[0177] The mixed form of PTFE can be prepared by (1) mixing an aqueous dispersion of PTFE with an aqueous dispersion or solution of an organic polymer and co-precipitating to obtain a co-aggregated mixture (methods described in JP-A-60-258263, JP-A-63-154744, etc.), (2) mixing an aqueous dispersion of PTFE with dried organic polymer particles (method described in JP-A-4-272957), or (3) homogeneously mixing an aqueous dispersion of PTFE with an organic polymer particle solution and simultaneously extracting each medium from the mixture. (4) a method of polymerizing a monomer that forms an organic polymer in an aqueous dispersion of PTFE (method described in JP-A-06-220210, JP-A-08-188653, etc.), and (5) a method of uniformly mixing an aqueous dispersion of PTFE and an organic polymer dispersion, and then polymerizing a vinyl monomer in the mixed dispersion, and thereafter obtaining a mixture (method described in JP-A-11-29679, etc.).
[0178] The proportion of PTFE in the mixed form is preferably 1 to 60% by weight, more preferably 5 to 55% by weight, in 100% by weight of the PTFE mixture. When it is within such a suitable range, good dispersibility of PTFE can be achieved.
[0179] When a fluorine-containing drip-preventing agent is contained as a flame retardant, the content is preferably 0.01 to 5 parts by weight, more preferably 0.05 to 1.5 parts by weight, and even more preferably 0.1 to 1 part by weight, relative to 100 parts by weight of component A. If the content of the fluorine-containing drip-preventing agent is less than 0.01 parts by weight, the flame retardancy may be insufficient, and if it exceeds 5 parts by weight, PTFE may precipitate on the surface of the molded article, resulting in poor appearance, and may also lead to an increase in the cost of the resin composition.
[0180] (Production of transparent antibacterial polycarbonate resin composition) Any method may be adopted to produce the transparent antibacterial polycarbonate resin composition of the present invention. For example, the A component, the B component, and optionally the C to E components and other additives are thoroughly mixed using a premixing means such as a V-type blender, a Henschel mixer, a mechanochemical device, an extrusion mixer, etc., and then the premix is granulated as necessary using an extrusion granulator or a briquetting machine, and then melt-kneaded using a melt kneader such as a vented twin-screw extruder, and then pelletized using a device such as a pelletizer.
[0181] (Production of molded articles made from transparent antibacterial polycarbonate resin compositions) The transparent antibacterial polycarbonate resin composition of the present invention can be injection molded from pellets obtained by the above-mentioned method to produce various molded products. In such injection molding, not only the usual cold runner type molding method but also a hot runner that enables runnerless production can be used. In addition, in the injection molding, not only the usual molding method but also gas-assisted injection molding, injection compression molding, ultra-high speed injection molding, injection press molding, two-color molding, sandwich molding, in-mold coating molding, insert molding, foam molding (including those using supercritical fluids), rapid heating and cooling mold molding, heat insulating mold molding, and in-mold remelting molding, as well as molding methods consisting of combinations thereof, can be used.
[0182] The resin composition of the present invention can also be used in the form of various profile extrusion molded products, sheets, films, etc. by extrusion molding. For molding sheets and films, inflation methods, calendaring methods, casting methods, etc. can also be used. Furthermore, it is possible to mold it into a heat shrinkable tube by subjecting it to a specific stretching operation. The resin composition of the present invention can also be made into a molded product by rotational molding, blow molding, etc.
[0183] Furthermore, molded articles formed from resin compositions can be subjected to various surface treatments, such as decorative painting, hard coating, water-repellent / oil-repellent coating, hydrophilic coating, ultraviolet absorbing coating, infrared absorbing coating, electromagnetic wave absorbing coating, heat-generating coating, antistatic coating, antistatic coating, conductive coating, and metallizing (plating, chemical vapor deposition (CVD), physical vapor deposition (PVD), thermal spraying, etc.).
[0184] (transparency) In the transparent antibacterial polycarbonate resin of the present invention, the haze value measured on a 2 mm-thick molded article made of the resin composition in accordance with JIS K 7136 is less than 50%, preferably less than 30%, and more preferably less than 10%.
[0185] (shock resistance) In the transparent antibacterial polycarbonate resin composition of the present invention, the notched Charpy impact strength of test pieces made of the resin composition conditioned at 23°C and -30°C in accordance with ISO179 was measured, and the respective values were 15 kJ / m 2 More than 20 kJ / m is preferable. 2 More preferably, 30 kJ / m or more. 2 If the thickness is less than the above-mentioned preferable range, it is difficult to apply the composition to outdoor structural members, various housing members, and automobile-related parts for cold regions.
[0186] (Antibacterial) In the transparent antibacterial polycarbonate resin composition of the present invention, the antibacterial activity value against Staphylococcus aureus and Escherichia coli in accordance with JIS Z 2801 for a test piece made of the resin composition is preferably 2.0 or more, more preferably 3.0 or more, even more preferably 4.0 or more, and particularly preferably 5.0 or more. If the antibacterial activity value is less than 2.0, it can be said that the antibacterial effect is insufficient. EXAMPLES
[0187] The present invention will be described in more detail below with reference to examples, but these are not intended to limit the present invention. Unless otherwise specified, parts in the examples are parts by weight and % is % by weight. Evaluations were performed according to the following methods.
[0188] 1. Evaluation of polycarbonate-polydiorganosiloxane copolymer resin (A-1 component) (1) Viscosity average molecular weight (Mv) The specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution of 0.7 g of polycarbonate-polydiorganosiloxane copolymer resin dissolved in 100 ml of methylene chloride. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls] The specific viscosity (η SP ) and the viscosity average molecular weight Mv was calculated using the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 Mv 0.83 c=0.7
[0189] (2) Polydiorganosiloxane component content and average chain length p+q Using NMR JNM-AL400 manufactured by JEOL Ltd., polycarbonate-polydiorganosiloxane copolymer resin 1 The average chain length p+q was calculated by measuring the H-NMR spectrum and comparing the integral ratio of the peak derived from the dihydric phenol (I) with the integral ratio of the peak derived from the hydroxyaryl-terminated polydiorganosiloxane (II). Similarly, the average chain length p+q was calculated by comparing the integral ratio of the peak derived from the hydroxyaryl-terminated polydiorganosiloxane with the integral ratio of the peak derived from the polydiorganosiloxane.
[0190] (3) Average domain size and normalized variance of polydiorganosiloxane domains Using a three-stage plate (width 50 mm, length 90 mm, thickness from the gate side 3.0 mm (length 20 mm), 2.0 mm (length 45 mm), 1.0 mm (length 25 mm)) prepared by the following method, the average size and particle size distribution (normalized dispersion) of the polydiorganosiloxane domains at the intersection 5 mm from the end and 5 mm from the side of the 1.0 mm thick part were measured using an X-ray diffraction device (Rigaku Corporation RINT-TTRII). The X-ray source was CuKα characteristic X-ray (wavelength 0.1541841 nm), tube voltage 50 kV, tube current 300 mA. The small angle scattering optical system was Slit: 1st 0.03 mm, HS 10 mm, SS 0.2 mm, RS 0.1 mm. The measurements were performed by asymmetric scanning (2θ scan) with FT 0.01° step, 4 sec / step, and scan range 0.06-3°. Curve fitting analysis was performed using the small angle scattering analysis software (Rigaku Corporation). The software NANO-Solver (Ver.3.3) was used for the analysis. The analysis was performed assuming that the spherical domains of polydiorganosiloxane are dispersed in a polycarbonate polymer matrix, and that there is a variation in the particle size distribution. The density of the polycarbonate matrix was set to 1.2 g / cm. 3 , the density of the polydiorganosiloxane domains is 1.1 g / cm 3 The experiment was carried out using an isolated particle model that does not take into account interparticle interactions (interparticle interference).
[0191] 2. Production of polycarbonate-polydiorganosiloxane copolymer resin (A-1 component) In the examples and comparative examples, the polydiorganosiloxane compound shown in (II)-1 below was used as the dihydric phenol (II) having a polydiorganosiloxane structure. (II)-1: p+q=40 (Shin-Etsu Chemical Co., Ltd.; KF-2201) PC-POS-1 and PC-POS-2 were produced in the following manner.
[0192] (PC-POS-1 manufacturing method) A reactor equipped with a thermometer, a stirrer, and a reflux condenser was charged with 21,592 parts of ion-exchanged water and 3,675 parts of 48.5% aqueous sodium hydroxide solution, and 3,880 parts (17.00 moles) of 2,2-bis(4-hydroxyphenyl)propane (bisphenol A) as the dihydric phenol (I) represented by the general formula [4] and 7.6 parts of hydrosulfite were dissolved therein. Then, 14,565 parts of methylene chloride (10 molar equivalents relative to the total amount of dihydric phenols) was added, and 1,900 parts of phosgene was blown in over a period of 60 minutes at 22-30°C with stirring. Add 7283 parts of methylene chloride (5 molar equivalents relative to the total amount of dihydric phenols), add 1131 parts of 48.5% aqueous sodium hydroxide solution, and add a solution of 108 parts of p-tert-butylphenol dissolved in 800 parts of methylene chloride (0.55 molar equivalents relative to the total amount of dihydric phenols), and add 430 parts (0.137 moles) of the above KF-2201 as dihydric phenol (II) represented by the general formula [5] dissolved in 800 parts of methylene chloride (0.55 molar equivalents relative to the total amount of dihydric phenols) at a rate of 0.0008 molar equivalents / min relative to dihydric phenol (I) to emulsify, then stir vigorously again. Under such stirring, add 4.3 parts of triethylamine when the reaction solution is at 26°C, and continue stirring at a temperature of 26-31°C for 1 hour to complete the reaction. After the reaction was completed, the organic phase was separated, diluted with methylene chloride, washed with water, and then acidified with hydrochloric acid and washed with water. When the conductivity of the aqueous phase was almost the same as that of ion-exchanged water, it was put into a kneader filled with warm water and the methylene chloride was evaporated while stirring to obtain a polycarbonate-polydiorganosiloxane copolymer powder. After dehydration, it was dried at 120°C for 12 hours in a hot air circulation dryer. In the obtained polycarbonate-polydiorganosiloxane copolymer, the average chain length p+q of the polydiorganosiloxane was 37, the viscosity average molecular weight was 20,100, the polydiorganosiloxane component content was 8.4% by weight, and the average domain size and normalized dispersion of the polydiorganosiloxane domains were 11 nm and 21.1%, respectively.
[0193] (PC-POS-2 manufacturing method) The manufacturing method was the same as that of PC-POS-1, except that the amount of p-tert-butylphenol was changed to 86 parts. In the obtained polycarbonate-polydiorganosiloxane copolymer resin, the average chain length p+q of the polydiorganosiloxane was 37, the viscosity average molecular weight was 24,100, the polydiorganosiloxane component content was 8.3% by weight, and the average domain size and normalized dispersion of the polydiorganosiloxane domains were 11 nm and 20.8%, respectively.
[0194] 3. Evaluation of transparent antibacterial polycarbonate resin composition (1) Transparency (haze) A three-tiered plate (width 50 mm, length 90 mm, thickness from the gate side 3.0 mm (length 20 mm), 2.0 mm (length 45 mm), 1.0 mm (length 25 mm)) created by the following method is used as a test piece, and the thickness of the test piece is 2. The haze at the 0 mm portion was measured. The transparency was evaluated according to the following criteria. ◎: Haze is less than 10% ○: Haze is 10% or more and less than 30% △: Haze is 30% or more and less than 50% ×: Haze is 50% or more
[0195] (2) Impact resistance (notched Charpy impact strength) Molded products (width 10 mm, length 80 mm, thickness 4.0 mm) prepared by the method described below were used as test pieces, and the notched Charpy impact strength of the test pieces conditioned at 23°C and -30°C was measured in accordance with ISO179. The impact resistance was evaluated according to the following criteria. ◎: Notched Charpy impact strength is 30kJ / m 2 End ○: Notched Charpy impact strength is 20 kJ / m 2 More than 30kJ / m 2 less than △: Notched Charpy impact strength is 15kJ / m 2 More than 20kJ / m 2 less than ×: Notched Charpy impact strength is 15 kJ / m 2 less than
[0196] (3) Antibacterial properties (antibacterial activity value) A square plate molded product (width 150 mm, length 150 mm, thickness 2 mm) prepared by the method described below was cut to obtain a test piece (width 50 mm, length 50 mm, thickness 2 mm). The test was conducted in accordance with 2801 under the following conditions. *Bacteria concentration: 1 / 500 normal bouillon medium (1 / 500NB) * Amount of bacterial solution dropped: 0.4 mL (covering film: surface area 16 cm 2 (Polyethylene film) *Culture temperature and humidity: 35℃, 90%RH *Culture time: 24 hours *Bacteria used: Staphylococcus aureus (NBRC12732), Escherichia coli (NBRC3972) *Cleaning method: Wipe with absorbent cotton soaked in ethanol The antibacterial properties were evaluated based on the antibacterial activity value according to the following criteria. Antibacterial activity value = log 10 (Number of live bacteria on untreated test pieces after 24 hours)-log 10 (Viable bacteria count on antibacterial test piece after 24 hours) ○: Antibacterial activity value is 2.0 or more against both of the above two types of bacteria. ×: Antibacterial activity value is less than 2.0 against at least one of the two types of bacteria used above. The antibacterial treated test piece refers to a test piece made of a resin composition containing a silver-based glass antibacterial agent, while the non-treated test piece refers to a test piece made of a resin composition containing the silver-based glass antibacterial agent but excluding only the silver-based glass antibacterial agent.
[0197] [Examples 1 to 17, Comparative Examples 1 to 4] The compositions of components A to E shown in Tables 1 and 2 were mixed uniformly using a blender, and then melt-kneaded using a vented twin-screw extruder to obtain pellets. A preliminary mixture of the components with the powder of the main component A was prepared in advance, with a concentration of approximately 10 to 100 times the amount of each component mixed, and the entire mixture was mixed using a blender. The vented twin-screw extruder used was a KTX-30 (diameter 30 mmφ) manufactured by Kobe Steel, Ltd. The extrusion conditions were cylinder temperature and die temperature 280°C, screw rotation speed 200 rpm, discharge rate 20 kg / h, and vent suction degree 3 kPa. Strands were extruded and cooled in a water bath, then strand cut using a pelletizer, and pelletized.
[0198] The obtained pellets were dried in a hot air circulation dryer at 120°C for 5 hours, and then molded products for various evaluations were produced using an injection molding machine (Sumitomo Heavy Industries, Ltd.; SE130EV-A) at a cylinder temperature of 280°C and a mold temperature of 70°C. Specifically, the following (a) to (c) were produced. (a) Three-stage plate: Width 50 mm, length 90 mm, thickness 3.0 mm from the gate side m (length 20 mm), 2.0 mm (length 45 mm), 1.0 mm (length 25 mm) (b) Molded product for Charpy impact test in accordance with ISO179: Width 10 mm, length 80 mm, thickness 4.0 mm (c) Square plate molding: width 150 mm, length 150 mm, thickness 2 mm The results of various evaluations are shown in Tables 1 and 2.
[0199] [Table 1]
[0200] [Table 2]
[0201] The symbols used for each component in Tables 1 and 2 are as follows: (Component A) A-1-1: PC-POS-1, refractive index 1.57 A-1-2: PC-POS-2, refractive index 1.57 A-2-1: Aromatic polycarbonate resin (linear aromatic polycarbonate resin powder having a viscosity average molecular weight of 19,700 and a refractive index of 1.59, with a repeating skeleton of 2,2-bis(4-hydroxyphenyl)propane) (manufactured by Teijin Limited; Panlite L-1225WX (product name)), A-2-2: aromatic polycarbonate resin (linear aromatic polycarbonate resin powder with a viscosity average molecular weight of 23,900 and a refractive index of 1.59, which has a repeating skeleton of 2,2-bis(4-hydroxyphenyl)propane) (manufactured by Teijin Limited; Panlite L-1250WP (product name)),
[0202] (B component) B-1: Silver-based glass antibacterial agent (manufactured by Sinanen Zeomic Co., Ltd.; Zeomic KM10D (product name)), average particle size (D50): 10 μm B-2 (for comparison): Antibacterial agent containing zinc-based glass and silver-based zirconium phosphate (product name: Novalon VFA701, manufactured by Toagosei Co., Ltd.), average particle size (D50): 1.2 μm In addition, the antibacterial agent of B-2 is zirconium phosphate carrying silver ions, which falls outside the scope of claim 1.
[0203] (C component) C-1: Phosphorus stabilizer (tris(2,4-di-tert-butylphenyl)phosphite) (manufactured by ADEKA Corporation; Adeka STAB 2112 (product name))
[0204] (D component) D-1: Glycerin monostearate (Riken Vitamin Co., Ltd.; Rikemal S-100A (product name)) D-2: Pentaerythritol tetrastearate (product name: Unistar H-476-S, manufactured by NOF Corporation)
[0205] (E component) E-1: Benzotriazole-based ultraviolet absorber (ADEKA Corporation; Adeka STAB LA-31 (product name)) E-2: Triazine-based UV absorber (manufactured by BASF Japan Ltd.; Tinuvin 1577ED (product name))
[0206] From Examples 1 to 17, it can be seen that the addition of the silver-based glass antibacterial agent described in claim 1 of the present invention to a mixture of polycarbonate-polydiorganosiloxane copolymer resin or polycarbonate-polydiorganosiloxane copolymer resin and other polycarbonate resin improves transparency and impact resistance, and also exhibits antibacterial properties. From a comparison between Example 2 and Comparative Example 4, it can be seen that when the silver-based glass antibacterial agent described in claim 1 of the present invention is added to a polycarbonate resin other than polycarbonate-polydiorganosiloxane copolymer resin, the impact resistance is inferior. Also, from a comparison between Example 2 and Comparative Example 4, it can be seen that in order to maintain transparency, it is necessary to use the silver-based glass antibacterial agent described in claim 1 of the present invention.
Claims
1. A transparent antibacterial polycarbonate resin composition comprising 100 parts by weight of (A) a polycarbonate-polydiorganosiloxane copolymer resin (component A-1) or a mixture (component A-2) of component A-1 and a polycarbonate resin other than component A-1 which comprises a repeating unit represented by the following general formula [1], and (B) 0.3 to 5 parts by weight of a silver-based glass antibacterial agent (component B) supported on glass so that silver ions having an average particle size (D50) of 7 to 15 μm as measured by a laser diffraction / scattering method are eluted, wherein the haze of a molded article having a thickness of 2 mm and made of the resin composition is less than 50%. 【Chemistry 1】 [In formula [1], R 1 and R 2 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each of these groups, they may be the same or different, e and f each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following formula [2].] 【Chemistry 2】 [In formula [2], R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of groups, they may be the same or different, g is an integer from 1 to 10, and h is an integer from 4 to 7.]
2. 2. The transparent antibacterial polycarbonate resin composition according to claim 1, wherein the component A-1 is a polycarbonate-polydiorganosiloxane copolymer resin containing a repeating unit represented by the following general formula [3]: 【Chemistry 3】 [In formula [3], R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number from 30 to 50. X is a divalent aliphatic group having 2 to 8 carbon atoms.]
3. In the above general formula [3], R 3 , R 4 , R 5 , R 6 , R 7 and R 8 3. The transparent antibacterial polycarbonate resin composition according to claim 2, wherein is a methyl group.
4. 4. The transparent antibacterial polycarbonate resin composition according to claim 2 or 3, wherein the repeating unit represented by the general formula [3] is a repeating unit derived from a (2-allylphenol)-terminated polydiorganosiloxane or a (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane.
5. 5. The transparent antibacterial polycarbonate resin composition according to any one of claims 1 to 4, characterized in that the content of the A-1 component is 5 to 100 parts by weight per 100 parts by weight of the total of the A-1 component and the A-2 component.
6. The transparent antibacterial polycarbonate resin composition according to any one of claims 2 to 5, characterized in that the content of the polydiorganosiloxane block represented by the general formula [3] is 0.5 to 20 wt % based on the total weight of component A.
7. 7. The transparent antibacterial polycarbonate resin composition according to any one of claims 2 to 6, characterized in that component A-1 has an aggregate structure in which polydiorganosiloxane domains are dispersed in a polycarbonate resin matrix, and the average size of the polydiorganosiloxane domains is 5 to 15 nm and the normalized dispersion is 25% or less.
8. 8. The transparent antibacterial polycarbonate resin composition according to any one of claims 1 to 7, characterized in that it contains, relative to 100 parts by weight of component A, 0.01 to 0.1 parts by weight of (C) a phosphorus-based stabilizer (component C), 0.1 to 1 part by weight of (D) a release agent (component D), and 0 to 1 part by weight of (E) an ultraviolet absorbing agent (component E).
9. A molded article obtained by molding the transparent antibacterial polycarbonate resin composition according to any one of claims 1 to 8.
Citation Information
Patent Citations
Antimicrobial polycarbonate resin composition
JP1994240125A
Antibacterial polycarbonate resin composition
JP1998168294A
Antistatic polycarbonate resin composition
JP1999323117A
Antibacterial mat and method for producing the same
JP2007217300A
Transparent thermoplastic resin composition excellent in antibacterial activity, and molded article composed thereof
JP2009299004A